VICTIMS ACCESS TO JUSTICE historical and comparative perspectives. - Cox, Pamela, 1970-; Walklate, Sandra ([S.l.] : ROUTLEDGE, 2022)
Why have many victim-centred policy initiatives met with so little success? How have those initiatives unfolded differently in different global jurisdictions over different periods of time? This book aims to address these questions. Building on a major research project exploring victims' access to justice over time and place, Victims' Access to Justice considers the potentialities for victims' participation in criminal justice systems and in victim programmes both in historical and comparative context. It considers a range of topics: ways of identifying and accommodating victims' needs and senses of justice; the impacts for criminal justice systems of seeking to accommodate these; and the ways in which adversarial criminal justice systems, in particular, may enable or inhibit victim participation. This is essential reading for all those engaged in understanding and working with victims of crime.
OCLC-licensed vendor bibliographic record.
Keywords: HISTORY / General; SOCIAL SCIENCE / Criminology; Victims of crimes; Criminal justice, Administration of